EKSPLORASI MATEMATIKA PADA PENDIDIKAN ANAK USIA DINI (PAUD) - Setiawan, Windi (Universitas Dr. Soetomo, 2018)
Mathematics carries an important role for life, mathematics is also useful for all sciences. That is why it is important to give (introduce) mathematics to kids since kindergarten age. This research is a descriptive study with qualitative approach that aims to describe the results of the analysis of mathematics learning in kindergartens. This research is expected to be able to be a literacy material to develop the curriculum in kindergarten. The subjects of this study were two kindergarten class B schools. Data collection was carried out by participatory observation, documentation, and interviews. Triangulation techniques are used to check data credibility. The results of this study are descriptions of the results of the analysis of mathematics learning in kindergarten which includes relationships and functions, arithmetic,geometri, statistic and determining the shortest distance.